Co Nanoislands Rooted on Co–N–C Nanosheets as Efficient Oxygen Electrocatalyst for Zn–Air Batteries. Issue 30 (6th June 2019) - Yu, Peng; Wang, Lei; Sun, Fanfei; Xie, Ying; Liu, Xu; Ma, Jingyuan; Wang, Xiuwen; Tian, Chungui; Li, Jinghong; Fu, Honggang
Abstract: Developing non‐precious‐metal bifunctional oxygen reduction and evolution reaction (ORR/OER) catalysts is a major task for promoting the reaction efficiency of Zn–air batteries. Co‐based catalysts have been regarded as promising ORR and OER catalysts owing to the multivalence characteristic of cobalt element. Herein, the synthesis of Co nanoislands rooted on Co–N–C nanosheets supported by carbon felts (Co/Co–N–C) is reported. Co nanosheets rooted on the carbon felt derived from electrodeposition are applied as the self‐template and cobalt source. The synergistic effect of metal Co islands with OER activity and Co–N–C nanosheets with superior ORR performance leads to good bifuctional catalytic performances. Wavelet transform extended X‐ray absorption fine spectroscopy and X‐ray photoelectron spectroscopy certify the formation of Co (mainly Co 0 ) and the Co–N–C (mainly Co 2+ and Co 3+ ) structure. As the air‐cathode, the assembled aqueous Zn–air battery exhibits a small charge–discharge voltage gap (0.82 V@10 mA cm −2 ) and high power density of 132 mW cm −2, outperforming the commercial Pt/C catalyst. Additionally, the cable flexible rechargeable Zn–air battery exhibits excellent bendable and durability. Density functional theory calculation is combined with operando X‐ray absorption spectroscopy to further elucidate the active sites of oxygen reactions at the Co/Co–N–C cathode in Zn–air battery. Abstract : A 3D hierarchical self‐supported electrode composed of Co nanoislands and Co–N–C nanosheets is developed for highly efficient bifunctional oxygen reduction reaction/oxygen evolution reaction catalysts toward both liquid‐ and solidstate Zn–air batteries. Operando X‐ray absorption fine‐structure is combined with density functional theory calculation to further elucidate the active sites of oxygen reactions at the Co/Co–N–C cathode in Zn–air batteries.